2018
DOI: 10.1002/adbi.201800042
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Microgels with Controllable Deformability Improve Healing Outcomes

Abstract: Platelets mediate hemostasis by aggregating and binding to fibrin to promote clotting. Over time, platelets contract the fibrin network to induce clot retraction, which contributes to wound healing outcomes by increasing clot stability and improving blood flow to ischemic tissue. In this study, we describe the development of hollow platelet-like particles (PLPs) that mimic the native platelet function of clot retraction in a controlled manner and demonstrate that clot retraction-inducing PLPs promote healing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…15 Like native activated platelets, these particles are capable of a high degree of deformability, as indicated by atomic force microscopy (AFM) characterization of ULC deformation on a glass surface. 16 Natural platelets have been shown to generate forces within fibrin matrices, resulting in clot contraction and matrix stiffening; 3,4 however, the ability of PLPs to recapitulate this active force generation within fibrin matrices to generate bulk clot stiffening is not yet known. The effect of any potential PLP-induced clot stiffening upon fibroblast migration in vitro and corresponding healing in vivo has also not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…15 Like native activated platelets, these particles are capable of a high degree of deformability, as indicated by atomic force microscopy (AFM) characterization of ULC deformation on a glass surface. 16 Natural platelets have been shown to generate forces within fibrin matrices, resulting in clot contraction and matrix stiffening; 3,4 however, the ability of PLPs to recapitulate this active force generation within fibrin matrices to generate bulk clot stiffening is not yet known. The effect of any potential PLP-induced clot stiffening upon fibroblast migration in vitro and corresponding healing in vivo has also not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Nandi et al detailed the process of developing these PLPs and found that the ULC base particle is capable of deforming like an activated platelet, ULCs conjugated to fibrin-targeting antibodies to form PLPs are capable of generating contractile forces and enhancing fibroblast migration in vitro, and PLPs demonstrate enhanced wound closure rates in vivo over saline controls [101]. Additional studies have corroborated these results, as well as exhibited the antimicrobial activity of these PLPs when complexed with colloidal gold [19,100]. Another similar colloidal technology produced by Muhamed et al is injectable fibrin-based nanoparticles (FBNs) which have similar porosity and composition to the native clot structure and are designed to be integrated into clot assembly.…”
Section: Colloidal-based Wound Healing Materialsmentioning
confidence: 93%
“…Within these more established fields, there are numerous novel materials and methods in development that have the potential to shape the regenerative medicine field, including the use of bioactive scaffolds, hydrogels for cell delivery, and colloidal-based materials. Recent significant advancements include microporous annealed particle hydrogels for injection and in vivo crosslinking [76••], artificial microgels which recapitulate platelet function in vivo [19,100,101], and injectable pH-switchable scaffolds [102••]. The following sections will detail specific examples in these areas which have been demonstrated to be of potential benefit to wound reepithelialization and tissue remodeling.…”
Section: Novel Directions For Modulating the Wound Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to those optical properties, our target particles should also display a soft, ultralow crosslinked (ULC)‐like shell that could be coupled to fibrin‐biding proteins for artificial platelet applications. [ 27,41 ] Furthermore, the two chemistries (protein and dye coupling) should be chemo‐orthogonal, thereby removing the need for protection/deprotection chemistries.…”
Section: Introductionmentioning
confidence: 99%